Design, characterisation and validation of a haptic interface based on twisted string actuation - Skvortsova, Valeria; Nedelchev, Simeon; Brown, Joshua; Farkhatdinov, Ildar; Gaponov, Igor (Frontiers in Robotics and AI, 2022)
This paper presents design and experimental characterisation of a novel haptic interface based on a twisted string actuator. The interface is designed for controlled actuation of a human wrist joint and is capable of rendering wrist torque feedback through a rotary handle driven by twisted string actuator and spring loaded cable mechanisms. The interface was characterised to obtain its static and dynamic haptic feedback rendering capabilities. Compliance in the spring and actuation mechanism make the interface suitable for smooth rendering of haptic feedback of large magnitudes due to the high motion transmission ratio of the twisted strings. Haptic virtual wall rendering capabilities are demonstrated.